Review of Positive Law and Fiqh Law on Interfaith Marriages - Ahmad Azmi Perkasa Alam; M. Idris (ASIAN PUBLISHER, 2022)
This study describes a review of positive law and fiqh law on interfaith marriages. Marriage is the result of affection between men and women, so limiting marriage to religion is one of the conflicts that often occurs, interfaith marriage is something that is difficult to separate, especially those who adhere to the teachings of pluralism in Indonesia. So from here the researcher considers it important to raise the problems that occur in interfaith marriages, in this study the author uses a descriptive method, namely to provide data that is as accurate as possible about the problems discussed. This descriptive method is intended to get a good, clear and can provide data as accurately as possible about the object under study. Data collection techniques using library research techniques. The selection of literature is carried out as carefully as possible by considering the author's authority in the field under study. This study also examines in detail the law of interfaith marriage in terms of Islamic law following the as-Syafi'i school, and also links civil law and positive law in Indonesia, as well as the MUI fatwa.